Public administration : quest for identity - Bhaskara Rao, V.; Sharma, Arvind K.; Indian Institute of Public Administration (New Delhi : Vikas Pub. House, 1996)
In Indian context; papers presented at a seminar held at Indian Institute of Public Administration, New Delhi, 1992.
Includes bibliographical references and index.
Keywords: Public administration -- Study and teaching -- India -- Congresses; Public administration -- India -- Congresses; 80-13.